Application of gelatin-coated magnetic particles for isolation of genomic DNA from bacterial cells - Intorasoot S. (2014)
Gelatin-coated magnetic particles were implemented for bacterial genomic DNA isolation in this study. Based on structural differences in the cell wall, the standard strains Staphylococcus aureus and Escherichia coli were selected. The quantity, quality, and timing process for DNA extraction using gelatin-coated magnetite were compared to reference phenol-chloroform extraction and a commercially available kit. Approximately twice as much DNA was recovered with the use of coated magnetite, providing greater yields than other DNA extraction methods. In addition, the DNA quality was determined using 16S ribosomal DNA (rDNA) gene amplification by polymerase chain reaction (PCR). The described technique is rapid, simple, and a well-suited method to use with PCR for diagnosis of bacterial infections.